Pengaruh Pendapatan Pegadaian, Harga Emas, Dan Tingkat Inflasi Terhadap Penyaluran Kredit Cepat Aman (KCA) Pada PT. Pegadaian (PERSERO) Di Indonesia - Hardian Syahputra; Nurjannah Nurjannah; Salman Salman (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
The purpose of this study was to determine the effect of Pawnshop Income, Gold Prices and Inflation on Secure Fast Loan Distribution at PT. Pegadaian (Persero) in Indonesia. The type of research used is quantitative with time series data. The data analysis method used was multiple linear regression analysis using eviews 10 software. The results showed that pawnshop revenue had a positive and significant effect on the distribution of KCA at PT. Pegadaian (Persero) in Indonesia. The gold price has a positive and significant effect on KCA distribution at PT. Pegadaian (Persero) in Indonesia. Inflation has a negative and insignificant effect on the distribution of KCA at PT. Pegadaian (Persero) in Indonesia. Simultaneously, pawnshop revenue, gold prices, and the inflation rate have a positive and significant effect on the distribution of KCA to PT. Pegadaian (Persero) in Indonesia.